Risk-factors Associated With Poor Outcomes in VEO-IBD Secondary to XIAP Deficiency: A Case Report and Literature Review. Issue 1 (July 2019) - Lekbua, Asama; Ouahed, Jodie; O'Connell, Amy E.; Kahn, Stacy A.; Goldsmith, Jeffrey D.; Imamura, Toshihiko; Duncan, Christine N.; Kelsen, Judith R.; Worthey, Elizabeth; Snapper, Scott B.; Softic, Samir
Abstract : ABSTRACT: Very early onset inflammatory bowel disease (VEO-IBD) represents a diagnostic and treatment challenge. Here we present a case of VEO-IBD secondary to a mutation in BIRC4 gene, which encodes X-linked inhibitor of apoptosis protein (XIAP), in a 17-month-old boy with severe failure to thrive, intractable diarrhea, and hepatosplenomegaly. Endoscopy and histology identified only mild duodenitis and ileitis, but severe pancolitis with crypt abscesses and epithelium apoptosis. Minimal improvement in symptoms was achieved with total parenteral nutrition (TPN), intravenous (IV) corticosteroids, and tacrolimus, whereas induction and maintenance therapy with adalimumab led to complete remission. After 6 months, the patient developed hemophagocytic lymphohistiocytosis and eventually died due to multisystem organ failure. A review of the literature revealed that some patients with VEO-IBD secondary to XIAP deficiency develop symptoms that are refractory to medical and surgical management, while initial reports suggest that allogeneic hematopoietic stem cell transplantation (HSCT), with reduced intensity conditioning, can successfully induce long-lasting remission and may even be curative. We propose that in patients with XIAP deficiency a constellation of symptoms including colitis at an early age, severe failure to thrive, and splenomegaly/hepatosplenomegaly can identify a subgroup of patients at high risk of experiencing medically refractory IBD phenotype and increased mortality. Hematopoietic stem cell transplant should be considered early in these high-risk patients, as it may resolve both their intestinal inflammation and a risk of developing life threatening hemophagocytic lymphohistiocytosis . Abstract : Supplemental Digital Content is available in the text